Geographical information systems based site selection methodology for renewable energy systems in Palestinian territories - Buthayna Qutaina; Ahmad Shehada; Aysar Yasin; Mohammed Alsayed (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Renewable energy is the key term for the energy industry sector in the world recently. Palestinian territories (PT) have good potential for multiple renewable energy applications. The purpose of this study was to evaluate the potential sites for solar photovoltaic systems, concentrated solar power systems, and wind farms in the West Bank (WB). The study was derived from geographical information systems (GIS) and multi-criteria decision making (MCDM). The criteria for each application were identified and weighted according to the analytical hierarchy process (AHP). All the resulting layers were multiplied to produce the final suitability map for each application. The results of the study depend on two scenarios, In the first scenario, where area C is included, the areas classified as highly suitable for photovoltaic (PV), concentrated solar power (CSP), and wind turbines are between 14.27 and 7.56 km2. The second scenario is excluding area C, the highly suitable areas were between 4.1 to 2.47km2.